Autonomy as Dependence: Home-Based Education and Social Reproduction amongst Foreign Families in Bali - Molly Fitzpatrick (Humaniora, 2025)
This paper explores the phenomenon of home-based education among foreign families living in Bali, Indonesia. Drawing on ethnographic research with sixteen families who participate in homeschooling, unschooling, and/or worldschooling, it examines the ways in which their political, educational, and parenting practices become intertwined in their everyday lives. While they imagine themselves to be preparing their children for a deterritorialised, globally mobile future, these families articulate a sense of detachment from what they call "the system", most often referring to state institutions such as formal schooling, government regulation, and, at times, medical authorities. I argue that their daily practices are deeply entangled with, and reliant upon, the very structures they claim to reject.  This dynamic is mirrored in their parenting, which they describe as child-led and based on the core-value of autonomy, yet is in practice marked by relationality and dependence. Taken together, these paradoxes reveal how home-based education, rather than constituting a rupture from dominant systems, operates as a mode of social reproduction that sustains privilege and re-inscribes gendered and global inequalities.